1997
DOI: 10.1007/s11664-997-0222-5
|View full text |Cite
|
Sign up to set email alerts
|

New mechanisms in photo-assisted MOVPE of II-VI semiconductors

Abstract: The first detailed comparison has been made of the metalorganic vapor phase epitaxy growth rates of CdTe, ZnTe, and ZnSe, measured in situ with laser reflectometry. The comparison also includes the photo-assisted growth with visible radiation from an argon ion laser. Using a standard Group II precursor (DMCd or DMZn.TEN) partial pressure of 1.5 x 104 atm, VI/II ratio of I and DIPM (M = Te, Se) the maximum growth rates are in the region of 10 to 15 AU/ s. Decrease in growth rates of ZnTe at higher temperatures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…We suggest that the detected hydrogen originates mainly from pyrolysis products of the precursors. This suggestion is well supported by the results of Irvine et al 7 who showed that the hydrogen concentration in the samples varies considerably with the choice of precursors. In the present experiments a pronounced influence of the growth stoichiometry ͑Fig.…”
Section: B Hahn A) H Preis S Blü Mel and W Gebhardtsupporting
confidence: 79%
“…We suggest that the detected hydrogen originates mainly from pyrolysis products of the precursors. This suggestion is well supported by the results of Irvine et al 7 who showed that the hydrogen concentration in the samples varies considerably with the choice of precursors. In the present experiments a pronounced influence of the growth stoichiometry ͑Fig.…”
Section: B Hahn A) H Preis S Blü Mel and W Gebhardtsupporting
confidence: 79%
“…4 The concentrations of organometallics entering the reactor were measured using an Epison monitor and the growth rate and layer thickness measured in situ using laser interferometry. 4 The concentrations of organometallics entering the reactor were measured using an Epison monitor and the growth rate and layer thickness measured in situ using laser interferometry.…”
Section: Methodsmentioning
confidence: 99%
“…4,8 All these experiments were performed at 1:1 precursor VI:II ratio. This has been attributed to the decrease in beta hydrogen elimination, along with an increase in free radical mediated decomposition, with less steric hindrance for insertion of free radicals into the Se precursor.…”
Section: Hydrogen Incorporation In Undoped Znsementioning
confidence: 99%
See 1 more Smart Citation